The Delegitimization Cycle: How Toxic Leadership Erodes Employee Mental Health in Indonesian Workplaces - Burhanuddin (PT Maju Malaqbi Makkarana, 2026)
Toxic leadership has become a serious organizational issue in Indonesia, particularly within high power-distance workplace cultures that normalize abusive authority and discourage employee voice. Despite growing research on destructive leadership, studies exploring employees’ lived psychological experiences remain limited. This study investigates how toxic leadership contributes to emotional exhaustion, psychological distress, organizational silence, and fear among employees in Indonesian private-sector organizations. Using a qualitative phenomenological approach, data were collected through semi-structured interviews with nine informants and analyzed using thematic analysis. Findings reveal four major themes: delegitimization of employee agency, emotional exhaustion, organizational silence shaped by fear and hierarchy, and coping strategies ranging from adaptation to withdrawal and turnover intention. The study concludes that toxic leadership is reinforced by paternalistic and hierarchical organizational cultures, highlighting the need for stronger psychological safety, leadership accountability, and supportive workplace policies.